Blood lipid of preadolescent boys of well-to-do families - Muzief Munir; sudiro Darmoprawiro (Indonesian Pediatric Society Publishing House, 2017)
Coronary heart disease is presently one of the leading causes of death In adults in many countries, including in Indonesia. It is well known that elevated levels of cholesterol in children are closely associated with hypercholesterolemia and coronary heart disease in adult life. This study was conducted in an attempt to find a preliminary insight of the magnitude of the problem of hypercholesterolemia In children In Indonesia as a developing country. The blood lipid levels of 54 preadolescent boys from well-Io-do families were analyzed. Two-third of those children were shown to have elevated blood cholesterol level, and even one third or 16 out of 54 preadolescents boys investigated suffered from hypercholesterolemia. We conclude that elevated blood cholesterol level is frequently found among large-framed and obese Indonesian children.